2002
DOI: 10.1164/rccm.2105085
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Nasal Pressure for the Identification of Apneas/Hypopneas during Sleep

Abstract: The reference standard for identifying apneas and hypopneas is a pneumotachograph, but using this can disrupt sleep. Nasal airflow estimation by measuring nasal pressure via nasal prongs is better tolerated by patients. However, nasal pressure has not been validated, using an event-by-event analysis, for detecting apneas/hypopneas during sleep. Eleven patients undergoing polysomnography wore a nasal mask capable of measuring nasal airflow (via pneumotachograph) and nasal pressure simultaneously. Each study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 20 publications
0
44
0
2
Order By: Relevance
“…Moreover, its reliance on flow limitation leads to ambiguous results. Although we are currently using both techniques for clinical application, it is important to remember that some of the data in our study were gathered before nasal cannula was validated by Heitman et al (2002).The American Academy of Sleep Medicine (AASM) Task Force suggested that differentiation of apnoeas from hypopnoeas was not necessary in clinical practice because both event types share a common pathophysiology and clinical consequences (AASM 1999). The PSG register was analyzed over periods of 30 s and during sleep phases I, II, III, IV and rapid eye movement, according to R&K rules (Rechtschaffen and Kales 1968).…”
Section: Subjects and Signalsmentioning
confidence: 99%
“…Moreover, its reliance on flow limitation leads to ambiguous results. Although we are currently using both techniques for clinical application, it is important to remember that some of the data in our study were gathered before nasal cannula was validated by Heitman et al (2002).The American Academy of Sleep Medicine (AASM) Task Force suggested that differentiation of apnoeas from hypopnoeas was not necessary in clinical practice because both event types share a common pathophysiology and clinical consequences (AASM 1999). The PSG register was analyzed over periods of 30 s and during sleep phases I, II, III, IV and rapid eye movement, according to R&K rules (Rechtschaffen and Kales 1968).…”
Section: Subjects and Signalsmentioning
confidence: 99%
“…As expected, indices derived from the nasal pressure sensor alone were almost always larger than from the combina- AHI from a nasal pressure transducer and thermal sensor. 10,[29][30][31][32][33] Consistently, these studies reported the detection of a higher number of apneas when a nasal pressure transducer is used, compared with a thermal sensor, with differences ranging from 30% to 50%. 34,35 This is similar to this study, in which the mean difference between AI np and AI th was 5.3 (4.0, 6.7) events per hour (mean, 95% confidence interval), a difference of 51%.…”
Section: Signal Qualitymentioning
confidence: 58%
“…The nasal cannula responds rapidly and produces a close approximation of the flow past the cannula throughout the breath. 27,28 Nasal pressure transducers record only nasal airflow, meaning that they will overestimate the breathing disturbance in the presence of oral breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of general comparability of RIP and PNT is similar to conclusions of earlier studies. [17][18][19] Polysomnography is the current reference standard for the diagnosis of sleep disordered breathing. Technology that produces signals that accurately reflect respiratory flow and effort while remaining free of artifact is considered fundamental for reliable identification of abnormal respiratory events.…”
Section: Comparison Of Montage 1 and 3: Influence Of Using Pvdfb Withmentioning
confidence: 99%
“…Studies have shown that nasal pressure transduction agrees well with reference standard pneumotachography in the identification of apnea and hypopnea. 18,19 Thermistry has not proven to be a reliable measure of airflow, although, because of the high sensitivity and nonlinear response characteristics of the PNT, thermistry has been endorsed to distinguish obstructive apneas from hypopneas. 20,21 Currently, the AASM also recommends the use of RIP to determine breathing effort and as an alternative to NPT for hypopnea detection.…”
Section: Comparison Of Montage 1 and 3: Influence Of Using Pvdfb Withmentioning
confidence: 99%